Juzgado de Familia Número 6: autoficción, autorreferencialidad compleja y lo real - Causillas Fonseca, Tirso José (2022)
The paper explores the relationships between autofiction, scene and the Real based upon the insights generated in the creative process of the theater play Family Court Number 6 —an autofictional play that addresses the relationship between women and the Law in Perú— emphasizing the possibility of trauma as a creating and constructing force. To achieve these goals, on one hand I draw upon premises of artistic research, especially its self-reflective and critical dimensions. On the other hand, I assume autofiction as a narrative strategy that establishes the “self ” as being in permanent construction. Both paths intersect in what I choose to call complex self-referentiality. Finally, I reflect on trauma as the unrepresentable and as a boundary to creative practice.